Понятие “социальный круг” в истории социологии - Пипич, О. (Социология: теория, методы, маркетинг, 2000)
The term “social circle” is used primarily as an auxiliary term that helps to characterize
a social structure, designate the belonging of individuals to a certain social group or
another social formation. The one way to prove this term as sociological notion is
historical sociological analysis of social circle as a scientific term and a notion.
The main approaches in the history of sociology to the notion of “social circle” are
under analysis in paper. The author examines theoretical interpretations of this notion
by classics (F. Tönnies, G.Simmel) and neoclassics (P.Blau, J. Schepanski, analysts of
network analyses). The article gives a summary and generalization of their ideas about
social circle.